2020
DOI: 10.1007/s00428-020-02822-8
|View full text |Cite
|
Sign up to set email alerts
|

Testing for ROS1, ALK, MET, and HER2 rearrangements and amplifications in a large series of biliary tract adenocarcinomas

Abstract: Testing for ROS1, ALK, MET and HER2 rearrangements and amplifications in a large series of biliary tract adenocarcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
2
0
2
Order By: Relevance
“…ALK mutation status in CCA is an extremely rare condition as reported by Nai-Jung Chiang in 2016, showing that ALK rearrangement in CCA is present in 1/110 cases [ 41 ]. Similarly, Jeremy Augustin and colleagues in 2020 found no ALK translocations or amplifications in a study involving 73 intrahepatic, 40 perihilar bile duct, and 36 distal extrahepatic CCAs [ 42 ]. This rarity of ALK mutations in CCA makes patient recruitment for clinical trials challenging.…”
Section: Discussionmentioning
confidence: 99%
“…ALK mutation status in CCA is an extremely rare condition as reported by Nai-Jung Chiang in 2016, showing that ALK rearrangement in CCA is present in 1/110 cases [ 41 ]. Similarly, Jeremy Augustin and colleagues in 2020 found no ALK translocations or amplifications in a study involving 73 intrahepatic, 40 perihilar bile duct, and 36 distal extrahepatic CCAs [ 42 ]. This rarity of ALK mutations in CCA makes patient recruitment for clinical trials challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Из нарушений, затрагивающих ген MET, в опухолях билиарного тракта описаны амплификации и перестройки. Частота обоих видов нарушений невелика: для амплификаций она составляет 1-2 %, для перестроек -около 0,5 % [19,43,44]. На примере единичных клинических наблюдений была показана возможность успешного применения таргетных ингибиторов киназы MET при лечении опухолей билиарного тракта c геном MET, активированным посредством амплификации или транслокации [45,46].…”
Section: редкие генетические изменения в рецепторных тирозинкиназах: ...unclassified
“…Анализ амплификаций и транслокаций гена MET может производиться с использованием методов NGS или FISH. В качестве метода скрининга MET-амплификаций может использоваться ИГХ, однако этот подход, по-видимому, отличается достаточно низкой специфичностью [43].…”
Section: редкие генетические изменения в рецепторных тирозинкиназах: ...unclassified
“…Although there is insufficient evidence to recommend universal assessment, alterations for which targeted therapies exist and have been FDA-approved in other tumor types, including KRAS G12C mutation, [28][29][30] MET amplification, [31][32][33] and ALK, 34 RET, 35 or ROS1 fusions, 36 among others, 37 have been described with variable but overall rare frequency in biliary tract carcinomas and hepatocellular carcinoma. 38 However, limited data currently exist regarding the efficacy of targeted therapy in these situations, due to their rarity. In the phase I/II ARROW study, pralsetinib, a selective RET inhibitor, demonstrated an ORR of 57% in patients with RET fusionpositive tumors other than non-small cell lung cancer and thyroid cancer and who received prior treatment or were ineligible for standard therapies.…”
Section: Her2/erbb2 Overexpression/amplification/ Activating Mutationsmentioning
confidence: 99%